Finite mathematics for management, life, and social sciences - Barnett, Raymond A. (San Francisco, Calif. : Dellen Publishing Co., 1987)
The manual contains the solutions to the odd-numbered problems in each of the exercise sets, and the solutions to all of the problems in the chapter reviews.
Chapter 0. Preliminaries -- Chapter 1. Systems of linear equations; matrices -- Chapter 2. Linear inequalities and linear programming -- Chapter 3. Mathematics of finance -- Chapter 4. Probability -- Chapter 5. Additional topics in probability -- Chapter 6. Data description and probability distributions.
Keywords: MATHEMATICS; SOCIAL SCIENCES - MATHEMATICS; BIOMATHEMATICS